Pediatric Health Outcome Evaluation in Low-and Middle-Income Countries: A Scoping Review of NGO Practice - Jennifer Taylor RN, MScN; Paula Forgeron RN, PhD; Amanda Vandyk RN, PhD; Allen Finley MD, FRCPC, FAAP; Sophie Lightfoot RN, BScN (SAGE Publishing, 2021)
Objective. The purpose of this study was to explore the research on the delivery and evaluation of pediatric health services by non-governmental organizations in low-and middle-income countries to better understand how they contribute to positive and sustainable health outcomes. Methods. A scoping review was completed using a 2-step study selection procedure. Results. Of the 5742 studies, 17 met criteria, including quantitative and mixed method designs, representing 10 different non-governmental organizations with programs in 33 low-and middle-income countries. Health outcomes were reported 89 times across the studies. A total of 56 different outcomes were identified in total, of which 24 were positive, 27 were negative, and 5 were unchanged. Conclusions. Widespread variation between non-governmental organizations exist, however, comprehensive pediatric health outcome evaluation is growing. Further emphasis should be given to adolescent specific research and robust measurement of quality of life.